De la geopolítica de la dominación a las geografías políticas de la des/colonialidad del poder - Delgado Estrada, Juan Manuel (2019)
It is desired to open the debate within geography and its relationship with the social scienceson this dimensional milestone of the genesis of geography as a social science since Strabo, itsinstitutionalization in academia, its genesis as political geography of Darwinian biologicist origin, itslater mutation as geopolitics and its use as part of the expansionist policy of the imperial countries ofthe 19th century. Geography and his job as a geographer was transformed by geopolitics as a weaponof domination in the space and time of Europe and “Latin American”; Geopolitics and anarchistgeography were victims of the consequences of hegemonies in the academic and military field, thefirst was accused of conspiring in favor of the Nazis in World War II and the anarchist theory wasaccused by Marxism of not being rigorous scientifically, both were disappeared or banned from theacademy until recently. Geography from the horizon of meaning with modernity is also a means foremancipation or the “antidotes” as Morín would say to us from the same West, some geographies tograph from below and the earth as well as being more verb and not noun as Porto-Gonçalves wouldsay: The political geo-graphs of the des / coloniality of power.